Use of Probiotics to Control Biofilm Formation in Food Industries - Andreia R. Tomé; Fábio M. Carvalho; Rita Teixeira-Santos; Mette Burmølle; Filipe J. M. Mergulhão; Luciana C. Gomes (MDPI AG, 2023)
Microorganisms tend to adhere to food contact surfaces and form biofilms, which serve as reservoirs for bacteria that can contaminate food. As part of a biofilm, bacteria are protected from the stressful conditions found during food processing and become tolerant to antimicrobials, including traditional chemical sanitisers and disinfectants. Several studies in the food industry have shown that probiotics can prevent attachment and the consequent biofilm formation by spoilage and pathogenic microorganisms. This review discusses the most recent and relevant studies on the effects of probiotics and their metabolites on pre-established biofilms in the food industry. It shows that the use of probiotics is a promising approach to disrupt biofilms formed by a large spectrum of foodborne microorganisms, with Lactiplantibacillus and Lacticaseibacillus being the most tested genera, both in the form of probiotic cells and as sources of cell-free supernatant. The standardisation of anti-biofilm assays for evaluating the potential of probiotics in biofilm control is of extreme importance, enabling more reliable, comparable, and predictable results, thus promoting significant advances in this field.